The importance of cryotherapy in rehabilitation - Derewiecki, Tomasz; Mroczek, Krzysztof; Duda, Marta; Majcher, Piotr (Polish Journal of Public Health, 2013)
Introduction. Cryotherapy reduces the swellings, the production of irritants and pain. It is applied to treat many different diseases, as well as surgical treatments. It has become more and more common and accessible form of therapy.Aim. The aim of the present work was to check the availability of cryotherapy in rural and urban areas.Material and methods. The study involved 102 patients of Zamość Rehabilitation Center of University of Management and Administration, including 68 women (66.67%) and 34 men (33.33%). The research tool was an author’s questionnaire survey.Results. Availability of cryotherapy according to 55.88% of the respondents is sufficient, whereas 44.12% of respondents believe that it is insufficient. Sufficient availability of cryotherapy was reported by 54% of respondents living in the urban area and 56% - in rural area. Most patients use the cryotherapy treatments in non-public healthcare centers (NZOZ).Conclusions. Cryotherapy is a treatment more and more commonly available, both for those living in rural and urban areas. Doctors prescribing cryotherapy should pay special attention to contraindications and coexisting diseases